The utilization of YouTube by Gen Radio as content distribution alternative channel - Rohim, Syaiful (Manajemen Komunikasi, 2024)
The rapid development of the Internet allows all users to distribute videos in a broader range to social media platforms such as YouTube because on this platform, the users can freely choose what content they want to watch, especially music. Therefore, many broadcast industries utilize YouTube to distribute their content. This research aims to understand how Gen 98.7 FM radio utilizes YouTube media as an alternative content distribution. The theory used is the New Media theory, which Pierre Levy developed, and it is said that new media is the development of media from the conventional to the digital era. This research uses a qualitative approach and descriptive research type. Data collection techniques were done by using interviews, observation, and documentation. The results of the study showed that the utilization of YouTube radio Gen 98.7 FM as an alternative content distribution is an amplification of on-air radio. It is also to introduce radio to the digital, which is packaged and distributed to the featured program through a YouTube channel. By utilizing YouTube, Radio Gen 98.7 FM gets more listeners because those who watch YouTube do not necessarily listen to the radio and vice versa.